2018
DOI: 10.1177/1120700018768615
|View full text |Cite
|
Sign up to set email alerts
|

Higher UHMWPE wear-rate in cementless compared with cemented cups with the Saturne® Dual-Mobility acetabular system

Abstract: At short term follow-up, the mean wear-rate in old and low demand patients was high, correlated to activity, and was above the generally accepted osteolysis threshold (0.1 mm/yr.). Cementless HA-coated cups had higher wear-rate than cemented cups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…An in vivo study with ultra-high molecular polyethylene dual mobility bearings showed that rates of wear of more than a threshold of 0.1 mm/year may risk the development of osteolysis. 40 More recently, a radioisometric analysis of highly cross-linked polyethylene showed no higher rates of wear than with traditional single bearings. 41 However, comparison of wear is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study with ultra-high molecular polyethylene dual mobility bearings showed that rates of wear of more than a threshold of 0.1 mm/year may risk the development of osteolysis. 40 More recently, a radioisometric analysis of highly cross-linked polyethylene showed no higher rates of wear than with traditional single bearings. 41 However, comparison of wear is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dual mobility (DM) cups became increasingly popular in recent years, as they proved effective at preventing articular instability, by virtue of increased ‘jump distance’ and ratio of head-to-neck diameter [ 25 , 47 ]. Though the initial ‘Bousquet’ cup was prone to intra-prosthetic dislocations (IPD) and aseptic loosening [ 37 , 40 , 42 , 46 ], design improvements over the past decades resolved many shortcomings of DM cups, thanks to enhanced press-fit and bioactive coatings [ 10 , 31 ], as well as more durable liners made of ultra-high molecular weight polyethylene (UHMWPE) [ 37 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the remaining 86 articles were examined. Finally, according to the eligibility criteria, 56 articles were included in the systematic review [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure 1…”
Section: Resultsmentioning
confidence: 99%